Дослідження якості сушених капусти та кабачків під час зберігання - Євлаш, Вікторія Владленівна; Нєміріч, Олександра Володимирівна; Гавриш, Андрій Володимирович; Тарасенко, Тетяна Анатоліївна (My University, 2012)
У статті досліджено органолептичні властивості, сорбційні характеристики та мікробіологічні показники безпечності сушених капусти та кабачків під час зберігання. Обумовлено режими зберігання сушених овочів в різному пакуванні. The article examines the quality of dried squash and cabbage during storage in different types of packaging. As a result of determining the sensor properties of dried cabbage and squash as in not broken state, and in the form of powders found that after 6 months storage in plastic packaging dried slaw and sliced zucchini slices or chips lose their inherent smell and taste. Research sorption characteristics showed that the powder from cabbage to retain humidity 65 ... 72%. Found that powder with zucchini detects ability to absorb moisture less than powder from cabbage, because of various biological natures, and as a result, the chemical composition of the resulting product. Defined microbiological quality powders with cabbage and zucchini after 6 months storage in plastic packaging and 12 months. Dried vegetable as raw materials after storage in plastic packaging for 6 months and vacuum packaging within 12 months for microbiological quality does not exceed norms regulated drainage regulations to this group of products.
Keywords: сушена капуста; сушені кабачки; властивості; зберігання; dried cabbage; dried vegetable marrows; properties; storage; кафедра експертизи харчових продуктів; кафедра технології ресторанної і аюрведичної продукції; кафедра готельно-ресторанної справи